2017
DOI: 10.1016/j.jvs.2017.06.100
|View full text |Cite
|
Sign up to set email alerts
|

A current systematic evaluation and meta-analysis of chimney graft technology in aortic arch diseases

Abstract: Treatment of aortic diseases involving the aortic arch poses a great challenge. The CG technique has been applied as an alternative treatment option. This meta-analysis shows that endovascular repair of aortic arch disease using a CG technique in the aortic arch vessels is technically feasible and effective but not without major risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…Despite encouraging initial results, further studies are required to standardize this technique [19,20,21]. Chimney technique to extend the proximal landing zone in TEVAR is feasible in the majority of vascular centers, with satisfied midterm outcomes, but not without a risk of major complications [22][23][24][25]. Zhao et al [26] compared the outcomes of the chimney and hybrid technique for the reconstruction of a single arch branch and found that type Ia endoleak rate was significantly higher in the chimney group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite encouraging initial results, further studies are required to standardize this technique [19,20,21]. Chimney technique to extend the proximal landing zone in TEVAR is feasible in the majority of vascular centers, with satisfied midterm outcomes, but not without a risk of major complications [22][23][24][25]. Zhao et al [26] compared the outcomes of the chimney and hybrid technique for the reconstruction of a single arch branch and found that type Ia endoleak rate was significantly higher in the chimney group.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 11 publications involving 373 patients who underwent chimney endografts for their aortic arch disease (reported overall technical success rates of 91.3%, overall estimated proportion of early type 1a endoleak of 9.4% and retrograde type A dissection of 1.8%. The reported pooled 30-day mortality was 7.9%, with a reintervention rate of 10.6% and major strokes rate of 2.6% [30]. No long-term data exists regarding the durability of the chimney graft in the aortic arch.…”
Section: Chimney Grafts/parallel Graft/periscopementioning
confidence: 99%
“…Balloon expandable stents are preferable to self-expanding due to their accurate deployment and higher radial force [29]. Chimneys are mostly performed for acute emergency reasons such as dissection, IMH and pseudoaneurysm, with the commonly used proximal landing zone site is in zone 2, and frequently done for a single vessel [30]. This technique is relatively cheaper to use, and it is perceived as less technically demanding [7].…”
Section: Chimney Grafts/parallel Graft/periscopementioning
confidence: 99%
“…The principal advantage of this off label technique is in its use of off-theshelf components and techniques familiar to most operators to achieve a more proximal landing zone during arch TEVAR. The disadvantage of this technique is the creation of gutters around the aortic endoprosthesis with a 6.4-9.4% rate of type IA endoleak (24,25).…”
Section: Repair With Parallel Graftsmentioning
confidence: 99%